Fabrication and Characterization of Lercanidipine Hydrochloride Solid Dispersions by Fusion Technique: Pharmaceutical Science-Pharmaceutics for effective drug dosage - Nazemoon Reddy; Swarnalatha Dugasani; Devanna Nayakanti (International Journal of Life Science and Pharma Research, 2022)
The authors aimed to design solid dispersions with Lercanidipine Hydrochloride (LCD) with PVP K-30, Poloxamer-188, and HPMC K4M as carriers. Various mixtures of LCD and Polymers (PVP K-30, Poloxamer-188, and HPMC K4M) were made in 1:1, 1:3, 1:5 and 1:7 ratios, and the solid dispersion was prepared by melting tactic, later compressed into tablets. Drug excipient compatibility studies were examined by DSC and FTIR studies. LCD was found to compatible with carriers used. The LCD solid dispersion was measured for physicochemical quality both in solid dispersions SD, and tablet states. The LCD solid dispersions found to have excellent flow possessions and compression assets. The yield of prepared solid dispersion was observed to be more than 90%), and the formulation LPOX-3 has showed a good yield of 98.9±1.95%, The tablets which were compressed from solid dispersions were found to have a uniform in size, shape, color, and consistency. The tablets were observed to have a uniform in thickness, and weight and ranged from 300.2±1.64 to 301.7±1.64 mg. The loss on friability was less than 1%, and the hardness was more than 4 Kg/cm2 indicates significant mechanical strength and the LCD content was also found to be uniform (96.8±1.35 to 99.9±2.34). The solubility of LCD was found to be good in 0.1N HCl and diminished with an increase in pH of the buffer. LCD released from the tablets were firstly by eruption followed by zero order. The dissolution was found to be good in solid dispersions with LCD: Poloxamer-188 at the ratio of 1:5. The results obtained were satisfactory. The study concludes that LCD solid dispersions (LPOX-3) with 1:5 ratios of LCD and Poloxamer-188 was found to be a better carrier than PVP K-30, and HPMC K4M in increasing the solubility of LCD from the solid dispersions.